Occult ovarian clear-cell carcinoma diagnosed as primary adenocarcinoma of the lung: A case report of a diagnostic pitfall for clinicians and pathologists. (2018) - Kubo, Terufumi; Hirohashi, Yoshihiko; Fujita, Hiromi; Sugita, Shintaro; Kikuchi, Yasuhiro; Shinkawa, Tomoyo; Nakatsugawa, Munehide; Tsujiwaki, Mitsuhiro; Sudo, Yuta; Asai, Yuichiro; Umeda, Yasuaki; Takahashi, Hiroki; et al.
Abstract: We present a case of ovarian clear-cell carcinoma that was initially diagnosed as adenocarcinoma of lung origin. This is an instructive diagnostic pitfall for clinicians and pathologists because of the unusual clinical course, small biopsy material, and noteworthy immunophenotype of the carcinoma. Imaging analysis identified only lung and liver lesions. In addition, the biopsy specimen from the lung was TTF-1 negative and napsin A positive, which is still possible for cancer of lung origin. Postmortem examination found that the cancer should be classified as ovarian clear-cell carcinoma distinguished by positive staining for napsin A and paired-box gene 8 (PAX8). Although PAX8 may not be usually investigated when tumoral lesions are identified in only the lung and liver, it is important to keep the necessity of PAX8 in mind to excluding carcinoma of Müllerian, renal, or thyroid origin.